PERUBAHAN DISTRIBUSI MERKURI (Hg) TERHADAP WAKTU DI SEDIMEN SUNGAI POBOYA - Febrianti, I; Ratianingsih, R; Puspita, J W (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2018)
Poboya is illegal gold mining area at Palu City. The amalgamate process of gold extraction is prepared traditionally using mercury. Tailing of this process which contains mercury is throwed away to the ground. The mercury contain will infiltrate to the soil water and later on pollute Poboya’s river. Related to the mercury that categorized as dangerous material, this research  purposes to investigate the mercury distribution changing at Poboya’s river sediment. The mercury distribution changing is investigated by modify the advection-diffusion equation model. The model was completed by the initial conditions and Neumann boundary conditions. To get the numerical solutions, it is used a numerical scheme namely Duffort Frankel finite difference method for the second derivative, and Center Scheme for the first derivative. The solution represents the mercury distribution changing with respect to time at the Poboya’s river sediment. The simulation result explains that 0,0521 ppm mercury is distributed from the upper bound (current source) observation domain following the sediment direction (to estuary) caused by the advection process and decreased due to the diffusion process. For , the mecury was distributed  0,00285 m to the estuary direction with the mercury concentration is 0,005 ppm, until , mercury was distributed 0,00832 m to estuary with mercury concentration is 0,005 ppm. In fact that at the estuary (lower bound), the 0,0244 ppm mercury that was already deposited will be diffused in an opposite direction. The advection process and the low initial mercury concentration, makes the reached distribution distance is no longer far comparing to the opposited mercury distribution. For   the mercury was distributed 0,000822 m to the upper direction with mercury concentration is 0,005 ppm, until , the mercury was distributed 0,000873 m with mercury concentration is 0,005 ppm